Experimental Evaluation of Karappan Chooranam in the Management of Pitha Karappan - Miraaj, R.; Sivashanmugarajah, S. (Postgraduate Institute of Indigenous Medicine, 2026)
Karappan is one of the intrinsic skin disorders described in Siddha medicine and is extensively mentioned in the Siddha pediatric textbook Balavakadam. Pitha Karappan (PK) is considered a subtype of Karappan and its clinical manifestations are comparable to Atopic Dermatitis described in contemporary allopathic medicine. According to Siddha literature, PK can be effectively managed using traditional Siddha polyherbal formulations. The present study aimed to evaluate the antihistaminic activity of the Siddha formulation KC, mentioned in Sarabenthira Vaidhya Muraigal - Karappan Viranaroga Sikichai for the management of PK. The study protocol was approved by the Institutional Animal Ethics Committee of S. A. Raja’s College of Pharmacy. The antihistaminic activity was evaluated through an in vivo animal experiment using Swiss albino mice. The bar test method was employed to assess clonidine-induced catalepsy and determine the indirect antihistaminic activity of the formulation. The animals were randomly divided into five groups: one control group of three animals and four experimental groups of four animals each. The experimental groups were pretreated with KC at doses of 100, 200, and 300 mg/kg, respectively, while the standard group received chlorpheniramine maleate (10 mg/kg). Clonidine (1 mg/kg) was administered 30 minutes after treatment. The control group exhibited maximum catalepsy (169 ± 0.21 seconds) at 90 minutes following clonidine administration. Pretreatment with KC at low, medium, and high doses, as well as chlorpheniramine maleate (10 mg/kg), showed a statistically significant reduction in clonidine-induced catalepsy (p<0.001). The findings of the study suggest that KC possesses significant antihistaminic activity and may be beneficial in the management of PK (Atopic Dermatitis).
Keywords: Atopic dermatitis; Clonidine-induced catalepsy; In vivo animal study; Karappan; Karappan Chooranam